Real time strategy robotic games / Hazrjen Nazman, Ahmad Syafiq Aiman A. Bakar and Izyan Auni Azme - Nazman, Hazrjen; A. Bakar, Ahmad Syafiq Aiman; Azme, Izyan Auni (2016)
The project is based on a tower defense and the competition is held by Malaysian Robotics Engineering Association (MREA). Nowadays, student (14-26) are not healthy because they are too obsessed with playing in computer games. Through this project of Real Time Strategy Robotic Game, the students will be attracted to play and joined this games. As is well known, the lack of physical activity participation among the students and letting the student use any gadget that is not healthy and make them fat and overweight. Therefore, the problem about the student to improve their physical and intellectual development in critical thinking had produced an idea to create Real Time Strategy Robotic Games. So for this project requires the construction of two self-contained remote controlled robot that can endure these obstacles yet fast enough to complete the objectives. There are two players in one team. To accomplish that, the players must devise their strategies to ensure victory. The cars have to hit all the three gates to win the game. This game will make people are more interested to play this Real Time Strategy Robotics Game.